(untitled) (Revista Justiça do Direito, 2021)
One of the main destinations for people who leave their homes whether voluntarily or forced is the European Union. It can be observed that both in voluntary and forced migrations, and especially in the second one, the European Union is the final destination of these displaced persons. However, the absence of an efficient migratory policy, has generated a chaotic scenario of illegal immigrants, disrespect for international regulations, and deprecated lives for economic reasons. The aim is to demonstrate that the EU’s asylum policy is not adequate and needs reform. Using the deductive approac h and bibliographic technique and data anal- ysis, the work presents the difficulties of a concise European Union policy on immigration and its effects in Poland.